Experience of learning from everyday work in daily safety huddles-a multi-method study - Karina Wahl; Margaretha Stenmarker; Axel Ros (BMC, 2022)
Abstract Background To reduce patient harm, healthcare has focused on improvement based on learning from errors and adverse events (Safety-I). Daily huddles with staff are used to support incident reporting and learning in healthcare. It is proposed that learning for improvement should also be based on situations where work goes well (Safety-II); daily safety huddles should also reflect this approach. A Safety-II-inspired model for safety huddles was developed and implemented at the Neonatal Care Unit at a regional hospital in Sweden. This study followed the implementation with the research questions: Do patient safety huddles with a focus on Safety-II affect the results of measurements of the patient safety culture? What are the experiences of these huddles amongst staff? What experiences of everyday work arise in the patient safety huddles? Methods A multi-method approach was used. The quantitative part consisted of a questionnaire (151 items), submitted on four different occasions, and analysed using Mann Whitney U-test and Kruskal Wallis ANOVA-test. The qualitative data were analysed using thematic content analyses of interviews with staff (n = 14), as well as answers to open questions in the questionnaires. Results There were 151 individual responses to the questionnaires. The response rates were 44% to 59%. For most comparisons, there were no differences. There were minor changes in patient safety culture measurements. A lower rating was found in December 2020, compared to October 2019 (p < 0.05), regarding whether the employees pointed out when something was about to go wrong. The interviews revealed that, even though most respondents were generally positive towards the huddles (supporting factors), there were problems (hindering factors) in introducing Safety-II concepts in daily safety huddles. There was a challenge to understanding and describing things that go well. Conclusions For patient safety huddles aimed at exploring everyday work to be experienced as a base for learning, including both negative and positive events (Safety-II); there is a need for an open and permissive climate, that all professions participate and stable conditions in management. Support from managers and knowledge of the underpinning Safety-II theories of those who lead the huddles, may also be of importance.